PSX-7 Differences of the carcass and non-carcass traits between divergent groups for residual feed intake in water buffaloes. (7th December 2018) - de Castilhos, A; Francisco, C; Jacaúna, A; de Barros, F; Marques da Silva, D; Aranha, A; Meirelles, P; Jorge, A
Abstract: The objective of this study was to evaluate differences between carcass and non-carcass traits and residual feed intake (RFI) of water buffaloes (Bubalus bubalis). Efficiency tests were performed in two-years of studies (2016 and 2017) in 173 non-castrated males (360 ± 77 kg of initial BW) of 3 genetic groups (GG): Jafarabadi (n = 53), Mediterranean (n = 60), and Murrah (n = 60). Animals were allocated during 84 days in collective feedlot pens equipped with automatic feeders and water trough (Intergado, Minas Gerais, Brazil). Residual feed intake was determined as the difference between the observed and predicted feed intake of the animals based on its metabolic BW and ADG. After the efficiency tests, animals were classified as Low (<0.5 SD mean; more efficient; n=36) and High (>0.5 SD mean; less efficient; n=42) RFI groups, and selected for measurement of the carcass and non-carcass traits. Data were analyzed using the MIXED procedure (SAS Inst. Inc., Cary, NC) and the Satterthwaite approximation to determine the denominator degrees of freedom for the tests of fixed effects. The model statement included GG, RFI groups, and their resulting interactions as fixed effects. Interaction was not detected (P > 0.10) between GG and RFI groups, thus, results are presented according to RFI groups. There were differences between RFI groups (P < 0.05) for blood, liver, lungs, empty gastrointestinal tract, and kidney, pelvic, and heart (KPH) fat which suggest differences in tissue metabolic activities, resulting in a divergence in some traits between RFI groups (Table 1). Similarities were observed between RFI groups for hot carcass weight, dressing percentage, and carcass edible portion (P > 0.10) whereas the proportions of bone and trimmable fat differed (P < 0.05). In conclusion, divergent groups of residual feed intake evaluated in water buffaloes present differences regarding carcass and non-carcass traits.